Instrumented Supply Chain and Interconnected Supply Chain on Operational Performance: The Role of Smart Technology - Zilnia Putri; Muhammad Ali Fikri (International Journal of Applied Business and International Management, 2025)
Transformation in the Industry 4.0 era has pushed manufacturing companies to adopt the latest technologies in their supply chains to enhance operational efficiency and productivity. This study aims to examine the influence of instrumented supply chain and interconnected supply chain on operational performance, with smart technology as a mediating variable. Data were collected using a purposive sampling method from 100 respondents of micro, small, and medium enterprises (MSMEs) in the manufacturing sector in Yogyakarta. The analysis was conducted using Smart PLS 4.0 software. The results reveal that the instrumented supply chain significantly influences operational performance (? = 0.546, p = 0.000) and smart technology (? = 0.515, p = 0.000). In contrast, the interconnected supply chain does not significantly affect operational performance (? = 0.052, p = 0.622), but has a significant effect on smart technology (? = 0.288, p = 0.011). Smart technology also significantly improves operational performance (? = 0.304, p = 0.014) and mediates the effect of instrumented supply chain on operational performance (? = 0.156, p = 0.046). However, it does not mediate the effect of the interconnected supply chain on operational performance (p = 0.071). These findings highlight the strategic role of digital instrumentation and smart technology in enhancing supply chain-driven performance